Optimization of the medical aid to the relatives of vascular dementia patients - Podkorytov, V. (Journal of Education, Health and Sport, 2016)
Podkorytov V. Optimization of the medical aid to the relatives of vascular dementia patients. Journal of Education, Health and Sport. 2016;6(11):795-801. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.344533 http://ojs.ukw.edu.pl/index.php/johs/article/view/4299 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016. OPTIMIZATION OF THE MEDICAL AID TO THE RELATIVES OF VASCULAR DEMENTIA PATIENTS V. Podkorytov State Enterprise ”Institution for Neurology, Psychiatry and Narcology under National Academy of Medical Sciences of Ukraine”, Kharkov, Ukraine psychotipe@gmail.com Abstract The objective: to identify methods of optimization of medical, psychological and social assistance to the relations, taking care for vascular dementia patients. Three groups of problems have been marked in the persons under investigation, they are: socio-psychological, financial, and legal. The relations of dementia patients have fill in questionnaires later on studied carefully. On the basis of the data obtained some ways of medical aid optimization to vascular dementia patients and their families have been. Key words: vascular dementia, relatives of a patient, social, psychological and legal problems.